Efektivitas Edukasi Melalui Media Leaflet terhadap Peningkatan Pengetahuan Remaja Putri Tentang Risiko Pernikahan Dini - Aat Maptukhah; Nur Anita (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
UNICEF in 2019 said there are around 115 million boys married under the age of 18. According to UNICEF in 2021, the most marriages of underage girls before the age of 18 in the world occurred in Nigeria, accounting for 76%. Chad and the Central African Republic rank next at 61% and Mali at 54%. Indonesia is ranked second with early childhood in ASEAN after Kambojo and ranked 8th in the world for child marriage cases. The impact of early marriage, maternal safety due to childbirth, and children born are also at risk of death in new babies, BBLR and stunting. Theresearch is to know theeffectiveness of education through leaflets to increase adolescent knowledge about the risks of early marriage. The research method uses experimental Quasi with one group pretest-posttest design. The sample in this study was all young women who lived in Saga Balaraja Village, Tangerang in December 2022, as many as 48 people. So the sampling in this study was total sampling. The results of the study onthe frequency of knowledge of respondents before being given education through leaflet media were mostly knowledgeable less than 75.0% and after being educated most young women were well informed 58.3%. There is an effectiveness of education through leaflets on increasing young women's knowledge about the risks of early marriage (p. value 0.000). Theconclusion of this study is ada effectiveness of education through leaflets on increasing the knowledge of young women about the risks of early marriage. It is hoped that there will be cooperation with health workers to provide health education about the risks of early marriage.